The clinical spectrum of reactions developed based on paraphenylenediamine hypersensitivity two pediatric cases - Nacaro?lu, Hikmet Tekin; Yavuz, Sinan; Basman, Eray; Bahçeci, Semiha Erdem; Taşdemir, Mehmet; Yi?it, Özgül; Can, Demet (Termedia Publishing House, 2015)
Paraphenylenediamine (PPD) is a blue-black aniline dye commonly used in hair dyes. It is also used in textile and fur dyes, wool dye, dark cosmetics, temporary tattoo hennas, photo baths, and photocopy and printing ink. Paraphenylenediamine, which accelerates the absorption of hair dye and henna tattoos by the skin and helps the formation of the black color, is an allergen. Paraphenylenediamine leads to hypersensitivity reactions, involving allergic and irritant contact dermatitis [1–3]. Since tattoo and hair dyes are now frequently used in younger children, complications of these applications (which are considered harmless and temporary) are appearing in children. In this study, two pediatric patients who presented to our department with clinical symptoms similar to angioedema and allergic contact dermatitis are discussed.
WOS: 000365404500012
PubMed ID: 26759549
Keywords: Clinical Spectrum; Pediatric Cases